Constructing a critical thinking evaluation framework for college students majoring in the humanities - Li, Suqi; Tang, Shenyu; Geng, Xingyu; Liu, Qi (Frontiers in Psychology, 2022)
Education for Sustainable Development (ESD) has focused on the promotion of sustainable thinking skills, capacities, or abilities for learners of different educational stages. Critical thinking (CT) plays an important role in the lifelong development of college students, which is also one of the key competencies in ESD. The development of a valuable framework for assessing college students’ CT is important for understanding their level of CT. Therefore, this study aimed to construct a reliable self-evaluation CT framework for college students majoring in the humanities. 642 college students majoring in the humanities were collected. The sample was randomly divided into two subsamples (n1 = 321, n2 = 321). The first sample was used for exploratory factor analysis (EFA) and the other for confirmatory factor analysis (CFA). After the EFA, the CT abilities evaluation scale included 7 factors, namely discipline cognition, motivation, open-mindedness, attentiveness, clarification, organization skills, and reflection. The Cronbach’s alpha coefficient for the whole scale was .909, and the values of the Cronbach’s alpha coefficients for individual factors of the scale ranged from .724 to .878. Then CFA was conducted within the scope of the validity study of the scale. In this way, the structure of the 7-factor scale was confirmed. Results indicated that the constructed evaluation framework performed consistently with the collected data. CFA also confirmed a good model fitting of the relevant 22 factors of the college students’ CT framework (2/df = 3.110, RMSEA = 0.056, GFI = 0.927, AGFI = 0.902, NFI = 0.923, and CFI = 0.946). These findings revealed that the CT abilities self-evaluation scale was a valid and reliable instrument for measuring the CT abilities of college students in the humanities. Therefore, the college students’ CT self-evaluation framework included three dimensions: discipline cognition (DC), CT disposition, and CT skills. Among them, CT disposition consisted of motivation (MO), attention (AT), and open-mindedness (OM), while CT skills included clarification skills (CS), organization skills (OS), and reflection (RE). This framework can be an effective instrument to support college students’ CT measurement. Consequently, some suggestions are also put forward regarding how to apply the instrument in future studies.